2017
DOI: 10.1136/archdischild-2017-312962
|View full text |Cite
|
Sign up to set email alerts
|

Severe acquired subglottic stenosis in neonatal intensive care graduates: a case–control study

Abstract: SASGS is a serious consequence of intubation for mechanical ventilation in NICU graduates, especially in preterm infants. Minimising trauma during intubations, avoiding recurrent extubation/reintubations and using appropriate sized ETTs may help prevent this serious complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 34 publications
0
37
2
2
Order By: Relevance
“…Similarly, Thomas et al showed that longer duration of intubation was one of the factors that was associated with acquiring severe subglottic stenosis in neonates. 18 However, the number of intubation encounters, whether surgical or catherization, was not associated with acquisition of an airway abnormality or with the incidence of DI. This suggested that acquired lesions may have resulted from a direct surgical insult rather from repetitive airway instrumentation.…”
Section: Discussionmentioning
confidence: 88%
“…Similarly, Thomas et al showed that longer duration of intubation was one of the factors that was associated with acquiring severe subglottic stenosis in neonates. 18 However, the number of intubation encounters, whether surgical or catherization, was not associated with acquisition of an airway abnormality or with the incidence of DI. This suggested that acquired lesions may have resulted from a direct surgical insult rather from repetitive airway instrumentation.…”
Section: Discussionmentioning
confidence: 88%
“…There was no single case of de novo clinically significant acquired SGS with the use of cuffed endotracheal tubes in our institution over the last 5 years. Risk factors for subglottic stenosis such as multiple intubations, traumatic intubation, >1 weeks duration intubation, and low weight have been explored in previous studies . All eight patients with acquired SGS were premature neonates initially intubated with uncuffed tubes in neonatal ICUs outside our institution.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for subglottic stenosis such as multiple intubations, traumatic intubation, >1 weeks duration intubation, and low weight have been explored in previous studies. 2,[13][14][15] All eight patients with acquired SGS were premature neonates initially intubated with uncuffed tubes in neonatal ICUs outside our institution.…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric subglottic stenosis primarily results from two causes: iatrogenic injury and congenital deformities. While improvements in intubation techniques and neonatal care protocols have helped reduce the published rates of subglottic stenosis in neonates from nearly 8% to 0-2% since the 1970s, [1][2][3] it remains a commonly encountered, resourceintensive, and difficult-to-treat condition. Furthermore, traumatic intubation has been identified as an independent risk factor in the development of acquired subglottic stenosis (ASGS).…”
Section: Introductionmentioning
confidence: 99%